2009
DOI: 10.1007/s10620-009-1002-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Attenuates Reduced-Size Liver Ischemia–Reperfusion Injury But Impairs Liver Regeneration in Rats

Abstract: Long term, BMDCs could repopulate recipient's intestinal epithelium even without any special treatment, which suggests a novel insight into the maintenance of the intestinal epithelial constitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The I/R process leads to remarkable enhancement in the activities of these serum enzymes (Fig. 7d), proving that direct correlation between liver dysfunction and I/R process does exist, and the results are similar to literature reports 62,63 .…”
Section: Resultssupporting
confidence: 90%
“…The I/R process leads to remarkable enhancement in the activities of these serum enzymes (Fig. 7d), proving that direct correlation between liver dysfunction and I/R process does exist, and the results are similar to literature reports 62,63 .…”
Section: Resultssupporting
confidence: 90%
“…However, delayed liver regeneration has been reported in the initial phase after orthotopic liver transplantation [2729]. Furthermore, several previously published studies have shown a significant decrease in proliferating hepatocytes after treatment with mTOR inhibitors, based on the function of the phosphoinositide 3-kinase (PI3K) signaling pathway on survival, autophagy, and proliferation [2931]. Fouraschen et al showed that the mTOR inhibitor, rapamycin, regulated not only cell proliferation but also increased hepatic autophagy during liver regeneration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in MDA levels by the administration of rapamycin were detected in several studies. 28,29 Accordingly, it was shown that rapamycin reduced increased levels of NO in the rat brain. 29 Nevertheless, how rapamycin alleviates tissue insult in diabetic retinopathy remains tentative.…”
Section: Discussionmentioning
confidence: 99%